English Language Learners’ Experiences on the Factors Influencing Speaking - Sumbul, Sabiha; Neupane, Bharat Prasad; Kapar, Hiralal (GS Spark: Journal of Applied Academic Discourse, 2024)
Exploring the challenges and factors that impact the speaking skills of English language learners helps enhance their communication skills. This study examines English language learners’ understanding and experiences of the factors influencing speaking. For this purpose, we interviewed four participants, undergraduate students at different colleges in the Kathmandu Valley, Nepal. We analyzed their narratives thematically. The research results indicated that educational and institutional factors, personal motivation and practice, language environment and exposure, and technological exposure are the factors that affect the speaking of these English language learners. Participants' experiences revealed that they improved communication skills by utilizing language learning strategies such as using media and technology and practicing consistently.